INCREASE OF BODY WEIGHT IN CHILDREN AS A RESULT OF ADMINISTRATION OF MICRONUTRIENTS CONTAINING VITAMIN A: THE RESULTS OF PLACEBO-CONTROLLED STUDIES - R.T. Saygitov ("Paediatrician" Publishers LLC, 2008)
The results of trials studying influence of uncombined vitamin a and complex micronutrients containing retinol on children's body weight are analyzed in this article. Uncombined vitamin a doesn't influence on this rate. Micronutrients containing vitamin a administrated during 6 months (median) cause moderate but significant increase of body weight in children. This effect very largely concerned with increase of vitamin a concentration in blood plasma per 1,18 (0,12; 0,23)  mol/l or almost 20% from reference level. The study of results of meta-analysis showed that this result can be achieved with administration of 450 g of vitamin a daily (333-526 g daily) in complex with other micronutrients.Key words: children, body weight, vitamin a, meta analysis.